1985
DOI: 10.1115/1.3242436
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Method of Using Four-Hole Probes to Measure Three-Dimensional Flow Fields

Abstract: A simplified method of using four-hole probes to measure three-dimensional flow-fields is presented. This method is similar to an existing calibration and application procedure used for five-hole probes. The new method is demonstrated for two four-hole probes of different geometry. These four-hole probes and a five-hole probe are used to measure the turbulent boundary layer on a flat plate. The results from the three probes are in good agreement with theoretical predictions. The major discrepancies occur near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Normalization by P~ -/5 has been incorporated in the majority of the multihole probe calibration procedures developed in recent years (Treaster and Yocum, 1979;Westphal et al, 1987;Sitaram and Treaster, 1985).…”
Section: Pressure Coefficient Normalizationmentioning
confidence: 99%
“…Normalization by P~ -/5 has been incorporated in the majority of the multihole probe calibration procedures developed in recent years (Treaster and Yocum, 1979;Westphal et al, 1987;Sitaram and Treaster, 1985).…”
Section: Pressure Coefficient Normalizationmentioning
confidence: 99%
“…From the literature review of the calibration of five-hole probes, it is revealed that there are four ways to define non-dimensional pressure coefficients. Krause and Dudzindki (1969) first described the pressure coefficient normalization technique, for a five-hole probe with centre hole pressure labeled as 5 P and the off-axis holes labeled as 1 P , 2 P , 3 P and 4 P , the four pressure coefficients are given by (Treaster and Yocum, 1979;Sitaram and Treaster, 1985;Westphal et al, 1987). The advantage of this method lies in its simplicity and provides a good foundation to understand the operation of multi-hole probes.…”
Section: Pressure Normalization Techniquesmentioning
confidence: 99%
“…In use the stem was horizontal and the line of holes parallel to the vane wakes Fig. 10 Photograph of three-hole probe tip and stem and yaw directions) five-hole probes are the norm [20], although four-hole probes [21,22] are now almost as common; the main advantage of the latter is the smaller size, which is advantageous in transonic flows because the probe presents lower blockage. Because of the small size of the cascade, an unusually small probe capable of high-resolution measurements was required.…”
Section: Miniature Downstream Traverse Probe Geometrymentioning
confidence: 99%